2017
DOI: 10.1002/hep.29254
|View full text |Cite
|
Sign up to set email alerts
|

Human hepatocellular carcinomas with a periportal phenotype have the lowest potential for early recurrence after curative resection

Abstract: Hepatocellular carcinomas (HCCs) exhibit a diversity of molecular phenotypes, raising major challenges in clinical management. HCCs detected by surveillance programs at an early stage are candidates for potentially curative therapies (local ablation, resection, or transplantation). In the long term, transplantation provides the lowest recurrence rates. Treatment allocation is based on tumor number, size, vascular invasion, performance status, functional liver reserve, and the prediction of early (<2 years) rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
132
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(141 citation statements)
references
References 50 publications
9
132
0
Order By: Relevance
“…We showed that ASS1 belong to a set of genes from a periportal program expressed in sonic hedgehog HCA and downregulated in other molecular subgroups (Fig. ) . This data confirmed in human tumors the role of sonic hedgehog pathway in zonation previously observed in mouse models .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We showed that ASS1 belong to a set of genes from a periportal program expressed in sonic hedgehog HCA and downregulated in other molecular subgroups (Fig. ) . This data confirmed in human tumors the role of sonic hedgehog pathway in zonation previously observed in mouse models .…”
Section: Discussionsupporting
confidence: 85%
“…We hypothesized that GLI1 activation in shHCA could induce an alteration of the zonation program. In addition to ASS1 and ASL , we selected in the literature five other genes known to be expressed in periportal region ( HAL , SDS , GNMT , GLS2 and PCK1 ) and severn genes expressed in perivenous region ( CYP2E1 , CYP1A2 , RHBG , SLC22A12 , GLUL , LGR5 , AXIN2 ) . We assessed gene expression by quantitative reverse transcriptase polymerase chain reaction (RT–PCR) using Fluidigm technology and Taqman probes .…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have revealed that metastasis and recurrence are the most important reasons for the death of patients with HCC . Therefore, we examined the function of NCAPH in migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Gene set variation analysis (GSVA) is a nonparametric and unsupervised gene set enrichment method that can estimate the score of certain pathway or signature based on transcriptomic data (Hanzelmann et al , ). The 115 metabolism‐relevant gene signatures and seven HCC progression‐relevant signatures were achieved from previously published studies (Desert et al , ; Rosario et al , ), and by using gsva r package, each sample received 120 scores corresponding to 115 metabolism signatures and seven progression‐relevant signatures. Subsequently, differential analysis was conducted based on the 113 metabolism scores using limma package in r software, and the signatures with an absolute log2 fold change (FC) > 0.2 (adjusted P < 0.05) were defined as differentially expressed signatures.…”
Section: Methodsmentioning
confidence: 99%